Single cell and spatial sequencing define processes by which keratinocytes and fibroblasts amplify inflammatory responses in psoriasis - Ma, Feiyang; Plazyo, Olesya; Billi, Allison C.; Tsoi, Lam C.; Xing, Xianying; Wasikowski, Rachael; Gharaee-Kermani, Mehrnaz; Hile, Grace; Jiang, Yanyun; Harms, Paul W.; Xing, Enze; Kirma, Joseph; et al. (Nature communications, 2023)
The immunopathogenesis of psoriasis, a common chronic inflammatory disease of the skin, is incompletely understood. Here we demonstrate, using a combination of single cell and spatial RNA sequencing, IL-36 dependent amplification of IL-17A and TNF inflammatory responses in the absence of neutrophil proteases, which primarily occur within the supraspinous layer of the psoriatic epidermis. We further show that a subset of SFRP2 + fibroblasts in psoriasis contribute to amplification of the immune network through transition to a pro-inflammatory state. The SFRP2 + fibroblast communication network involves production of CCL13 , CCL19 and CXCL12 , connected by ligand-receptor interactions to other spatially proximate cell types: CCR2 + myeloid cells, CCR7 + LAMP3 + dendritic cells, and CXCR4 expressed on both CD8 + Tc17 cells and keratinocytes, respectively. The SFRP2 + fibroblasts also express cathepsin S, further amplifying inflammatory responses by activating IL-36G in keratinocytes. These data provide an in-depth view of psoriasis pathogenesis, which expands our understanding of the critical cellular participants to include inflammatory fibroblasts and their cellular interactions. Changes in Psoriasis and other inflammatory skin diseases during severity stages can be investigated using single cell and spatial transcriptomics. Here the authors compare different inflammatory skin diseases to emphasise differences in immune cells and inflammatory markers particularly keratinocytes and fibroblasts.